A comparative study on thermally and laser annealed copper and silver doped CdTe thin film solar cells. (October 2018) - Aris, Kamarul Azrul; Rahman, Kazi Sajedur; Ali, Ameen M.; Bais, Badariah; Yahya, Iskandar Bin; Akhtaruzzaman, Md.; Misran, Halina; Abdullah, Siti Fazlili; Alghoul, Mohammad A.; Amin, Nowshad
Highlights: Electrical performance of Cu doped CdTe thin films show better than Ag doped films to some extent. J-V characteristics demonstrates the preference of thermal annealing for higher efficiency. C-V measurement reveals low acceptor concentration of 1.5 × 1014 cm −3 . Laser annealed samples suggest stricter control of laser energy and focus to improve efficiency. Abstract: Copper (Cu) and silver (Ag) are the potential dopants that could enhance p-type doping of polycrystalline cadmium telluride (CdTe) thin films to be used in CdTe based solar cells. In this work, the effect of doping concentration of Ag and Cu in both thermal and laser anneal process of doping to CdTe thin film solar cells' electrical performance were investigated. CdTe thin films of 3 µm thickness were deposited using the close-spaced sublimation (CSS) process and subjected to Cu and Ag doping process through dip coating in copper (II) chloride (CuCl2 ) and silver nitrate (AgNO3 ) solution, respectively at different concentration range followed by either thermal or laser annealing. Thermally annealed CdTe thin films were treated in convection oven, whereas laser annealing was carried out by illuminating the samples with pulsed neodymium-doped yttrium aluminium garnet (Nd:YAG) laser at wavelength of 532 nm. Fabricated solar cells were electrically characterized by light current-voltage (J-V) and capacitance-voltage (C-V) measurements. J-V measurement demonstrates that Cu doped CdTe solar cells are having better electrical performance as compared to Ag doped ones. The effect of increasing dopant solution concentrations seems to have consistent trend with the increase of J-V parameters as identified in this work. C-V measurement shows that Cu doped CdTe films has higher doping capability with the highest acceptor concentration of 1.5 × 10 14  cm −3 compared to Ag doped CdTe films of 8.1 × 10 13  cm −3 . In addition, laser annealing finds lower J-V performance and acceptor concentration of Cu and Ag doped CdTe solar cells with limitations in smaller process space for surface annealing as well as optimization.